Adam Of The Road - Gray, Elizabeth Janet; Lawson, Robert (New York Puffin Books, 1942)
The adventures of eleven-year-old adam as he travels the open roads of thirteenth-century england searching for his missing father, a minstrel, and his stolen red spaniel, nick
American Corner
Awarded The John Newbery Medal
11
Keywords: English Fiction; English Stories